PENGARUH HARGA, KUALITAS PRODUK DAN KUALTIAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI UKM L.A MANYAR GRESIK: Price, Product Quality, Decision Decision - mochamad -; Fathoni, Achmad (GEMA EKONOMI, 2021)
Prices are all forms of monetary costs sacrificed by consumers to obtain, having utilized a number of combinations of goods and services of a product. A product is anything that can be offered to the market to get attention, use, or be consumed that can make up your desire or needs. Quality of service is a crucial issue for every company regardless of product form. The purpose of this study is to determine the effect of price, the effect of product quality and service quality on purchasing decisions. This population is consumers in L.A. Small and Medium Enterprises as many as 200 consumers in December 2019 and 135 samples were taken using theintintintal sampling model using the Slovin formula. The analysis technique uses multiple linear regression. The results showed that the price, product quality, service quality partially and simultaneously had a positive and significant effect on purchasing decisions. The results of each test as follows, the validity test r table 0.169, cronbach alpha reliability test 0.6, linearity test sig. Linearity of 0,000 and the value of deviation from linearity are 0.209, normality test with residual value of 0.381, autocorrelation test with DW value of 1.946, multicollinearity test of 0.934, heterocedasticity test of greater than 0.05 (5%), linearity test of 0.397, t-test of 0.934, F-test of 0.934, test of multicollinearity of 0.934, heterocedasticity test of greater than 0.05 (5%) 31,404. Ã‚Â  Keywords: Price, Product Quality, Decision Decision